A Clinical Update on Delirium: From Early Recognition to Effective Management. (16th June 2011) - Cerejeira, Joaquim; Mukaetova-Ladinska, Elizabeta B.
Abstract : Delirium is a neuropsychiatric syndrome characterized by altered consciousness and attention with cognitive, emotional and behavioural symptoms. It is particularly frequent in elderly people with medical or surgical conditions and is associated with adverse outcomes. Predisposing factors render the subject more vulnerable to a congregation of precipitating factors which potentially affect brain function and induce an imbalance in all the major neurotransmitter systems. Early diagnosis of delirium is crucial to improve the prognosis of patients requiring the identification of subtle and fluctuating signs. Increased awareness of clinical staff, particularly nurses, and routine screening of cognitive function with standardized instruments, can be decisive to increase detection rates of delirium. General measures to prevent delirium include the implementation of protocols to systematically identify and minimize all risk factors present in a particular clinical setting. As soon as delirium is recognized, prompt removal of precipitating factors is warranted together with environmental changes and early mobilization of patients. Low doses of haloperidol or olanzapine can be used for brief periods, for the behavioural control of delirium. All of these measures are a part of the multicomponent strategy for prevention and treatment of delirium, in which the nursing care plays a vital role.